Towards online repurchase intention: A non-probabilistic approach to unpack its antecedents in Pécs - Pobee, Frederick (Marketing & Menedzsment, 2021)
THE AIMS OF THE PAPER This research explores the determining factors of online repurchase of online shoppers in Hungary, focusing on Pécs. METHODOLOGY The non-probabilistic sampling technique (convenience sampling) was used to collect cross-sectional data from online shoppers in the city of Pécs. Data was collected from 412 online shoppers. In addition, SmartPLS – Structural equation modeling software was used to investigate the relationships of the hypothesized variables. MOST IMPORTANT RESULTS The research findings suggest that information quality, systems quality, and service quality significantly affect user satisfaction. Consequently, user satisfaction was found to influence consumer repurchase intention significantly. RECOMMENDATIONS The findings present some practical implications for e-vendors and online business web designers. The significant influence of system quality on user satisfaction implies that e-vendors e-commerce web designers should provide quality website features that are reliable, user-friendly, has quick response time, and are available on a 24/7 basis. Also, to ensure user satisfaction and repurchase, e-vendors must give their consumers a satisfying online experience by providing the necessary support in real-time. Disputes from online transactions should be solved as quickly as they arise to the delight of consumers.